Information asymmetry, corporate governance, and IPO underpricing: Evidence in Indonesia - Pelawi, Jeffrey Bastanta; Pelawi, Rizky Yusviento (Jurnal Ekonomi dan Bisnis, 2023)
This paper analyzes the relationships between information asymmetry, corporate governance, and IPO underpricing in the Indonesian IPO market. Previous studies on underpricing IPO have shown mixed results, offering several interesting research gaps to explore, especially in emerging markets. Accordingly, the purpose of the research is to examine further whether information asymmetry and corporate governance are the causes of IPO underpricing. A purposive technique is used, and 318 samples of IPOs are selected from 2010 to 2020 on the Indonesian Stock Exchange (IDX). Next, a multiple regression model is developed and tested using the EViews 9 software. Our evidence shows that underwriter reputation negatively affects IPO underpricing, indicating a high level of information asymmetry in the Indonesian IPO market. Further, our evidence reveals that board size and number of employees negatively affect IPO underpricing. Meanwhile, manager and family ownership exhibit insignificant results due to the pyramidal ownership structure. Finally, we also find that reputable underwriters charge higher underwriting fees than non-reputable ones. In general, our study demonstrates that hiring a reputable underwriter and implementing good corporate governance practices can minimize underpricing during the IPO.